THE PROCESS OF QUALIFYING EMOTIONS AND AFFECTION IN EARLY CHILDHOOD EDUCATION: IMPLICATIONS AND POSSIBILITIES (Interdisciplinary Studies Journal, 2025)
The present research aimed to investigate the perception of early childhood education teachers regarding the qualification of emotions and affection, analyzing its implications and possibilities in educational practice. Its relevance is justified by the need for an integral early childhood education, which encompasses affective and emotional development. However, it is understood that, at times, these aspects may be erroneously interpreted, leading to their being unexplored or addressed incoherently, highlighting a latent demand for studies that broaden the discussion and propose possibilities and implications of such knowledge. For this purpose, the theoretical foundation is based on the assumptions of the critical-dialectical method, as well as the historical-cultural theory. As methodology, a bibliographic and field research was adopted, which included data collection through a questionnaire directed to early childhood education teachers from public and private schools in the municipality of Londrina - PR. The results indicate that the teachers recognize the importance of affective and emotional aspects for full child development. However, the evidence points to conceptual limitations that hinder the implementation of intentional pedagogical practices. Thus, the study proposes strategies to support teaching work, fostering the development of emotions and affection in early childhood education.
Keywords: Early Childhood Education; Teacher Education; Human Development; Emotions; Affection